Examination of the export-led growth hypothesis for Hong Kong and Singapore. - Lim, Ley Hoon. (2008)
This paper attempts to establish export-led growth hypothesis for Hong Kong and Singapore economies. Vector Autoregression, Cointegration and Vector Error Correction model are used to establish the export-income relationship and the direction of causality. We provided a comparision between the two economies.